Migration, Remittances, and Sustainable Development in Africa 2020
DOI: 10.4324/9780429288814-13
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and bribery in Africa

Abstract: This paper examines the effects of remittances on bribe payments to public officials to access public goods and services in Africa. We argue that migrant remittances may affect bribery among remittance recipients through the income and norm channels. Using Afrobarometer surveys administered in thirty-six African countries between 2004 and 2016, we find that remittance receivers are more prone to bribe payment than non-receivers. More importantly, we find that individuals who live in countries with higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“… 6 It may also well be that they use it for bribe payment to access public services. In line to this, a recent study by Konte and Ndubuisi (2020) showed among others, that remittance receivers are more prone to bribe payment than non-receivers.…”
supporting
confidence: 53%
See 1 more Smart Citation
“… 6 It may also well be that they use it for bribe payment to access public services. In line to this, a recent study by Konte and Ndubuisi (2020) showed among others, that remittance receivers are more prone to bribe payment than non-receivers.…”
supporting
confidence: 53%
“…Remittances underscore a closer link and communication between migrants and their loved ones that are left behind. Hence, remittance may serve as a conduit of internalized norms transfer or spillover from migrants to their loved ones either indirectly through communication and exchange, or directly as per when migrants inveigle their loved ones back home to comply with certain norms and beliefs by withholding transfer (Batista et al ., 2019; Konte and Ndubuisi, 2020; Levitt, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Remittance recipients having greater perceptions of higher insecurity or corruption do not drive support for military coups. Remittance recipients are found to have different views and experiences with crime and corruption (López García and Maydom 2021b; Konte and Ndubuisi 2020). A series of interaction results with neighborhood insecurity, corruption perception, and crime victimization did not yield significant results (tables –).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research find a statistical relationship between remittances and corruption but it is unclear as to whether international transfers help decrease or increase corruption (Abdih et al 2012; Ahmed 2013; Berdiev et al 2013; Tyburski 2012; 2014). Recipients can respond to greater corruption by voting out incumbents, disengaging from politics, or paying for the costs of corruption, such as bribery solicitations (Ahmed 2013; Konte and Ndubuisi 2020; Pfutze 2012; Tyburski 2014). However, it is unclear whether individual recipients will respond to corruption with antidemocratic preferences.…”
Section: Presidential Breakdowns and The Political Consequences Of Re...mentioning
confidence: 99%
See 1 more Smart Citation